A comparative study of pulmonary function between smokers and nonsmokers of rural population of Katihar, Bihar, India - Kumar, Rakesh; Suman, Shanker (International Journal of Advances in Medicine, 2017)
Background: In India, where majority of the population lives by agriculture and linked occupations in rural areas despite of rapid increase in urban population, the pulmonary function is expected to vary between smokers and non-smokers. Methods: This study was carried out in the rural population of Katihar, Bihar in 100 participants. Prior consent was obtained from the Ethical committee for the study. Computerized spirometer RMS Helios 701 was used for the study. Results: This study was done for a better understanding of effects of smoking in the rural population of Katihar. In rural non-smokers, the observed value of pulmonary functions in mean±standard deviation, FVC was 3.28±1.04 litres, FEV1 was 2.72±0.97 litres, FEV1% was 85.24±28.24, PEFR was 7.8±1.98 litres/minute, FEF25-75% was 4.28±0.99 litres. The observed value of pulmonary functions in rural smoker population in mean±standard deviation, FVC was 2.56±0.86 litres, FEV1 was 2.21±0.96 litres, FEV1% was 86.00±23.73, PEFR was 5.65±2.18 litres/minute, FEF25-75% was 3.34±1.37 litres. Conclusions: The comparative study of pulmonary function between rural smokers and rural non-smokers showed significant decreased value (p value < 0.05) in smokers of rural population.